2003
DOI: 10.1074/jbc.m310109200
|View full text |Cite
|
Sign up to set email alerts
|

The Intermediate S1′ Pocket of the Endometase/Matrilysin-2 Active Site Revealed by Enzyme Inhibition Kinetic Studies, Protein Sequence Analyses, and Homology Modeling

Abstract: Matrix metalloproteinases (MMPs, 1 matrixins) are believed to participate in angiogenesis, embryonic development, morphogenesis, reproduction, tissue resorption and remodeling, and tumor growth, progression, invasion, and metastasis through breakdown of the extracellular matrix, cell surface proteins, and processing growth factors, cytokines, and chemokines (1-3). Recently, human MMP-26 (endometase/matrilysin 2) was identified and its mRNA expression was detected in normal tissues of the human uterus and place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 44 publications
5
79
2
Order By: Relevance
“…Published research has shown that MMPs can promote tumor invasion through tissue barriers by degrading extracellular matrix and disrupting the basement membrane (36). MMP-26 can degrade most of the ECM components including fibronectin, vitronectin, fibrinogen, type IV collagen, gelatin, and non-ECM proteins including ·1-proteinase inhibitor and growth factor-binding protein 1 in vitro (11)(12)(13). Our study showed that MMP-26 expression contributes to the adherence and spreading ability of U251 cells on extracellular matrix components which contributes to the invasion process in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published research has shown that MMPs can promote tumor invasion through tissue barriers by degrading extracellular matrix and disrupting the basement membrane (36). MMP-26 can degrade most of the ECM components including fibronectin, vitronectin, fibrinogen, type IV collagen, gelatin, and non-ECM proteins including ·1-proteinase inhibitor and growth factor-binding protein 1 in vitro (11)(12)(13). Our study showed that MMP-26 expression contributes to the adherence and spreading ability of U251 cells on extracellular matrix components which contributes to the invasion process in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This special structural feature is to some extent a reflection of its unconventional enzyme activation mechanism, transcriptional regulation mechanism, and unusual function in physiological and pathological processes. MMP-26 can degrade most of the ECM components (11)(12)(13). MMP-26 can also activate proMMP-9 through cleavage of Ala93-Met94 site of the prepro-enzyme (14).…”
Section: Introductionmentioning
confidence: 99%
“…We used the same sequencing numbering as given by Park et al [4]. A homology modelling structure of MMP-26 was constructed based on the crystal structure of the catalytic domain of MMP-12 (cdMMP-12) [47]. A comparison of the MMP-26 structure with cdMMP-12 predicted three putative calcium-binding sites, designated C1, C2 and C3 in Figure 1(A) Wild-type pro-MMP-26 was auto-activated during folding by dialysis [4,8,40].…”
Section: Sequence Alignment and Homology Modelling Of Mmp-26mentioning
confidence: 99%
“…The homology modelling structure of the MMP-26 catalytic domain was constructed previously [47] using the SwissModel program [48]. The crystal structure of MMP-12 [33], which exhibits high similarity to MMP-26, was used as a template (PDB accession code 1JK3).…”
Section: Computer Modelling Of the Mmp-26 Catalytic Domainmentioning
confidence: 99%
See 1 more Smart Citation